Arterial enhancement pattern predicts survival in patients with resectable and unresectable intrahepatic cholangiocarcinoma. (March 2022) - Panettieri, Elena; Maki, Harufumi; Kim, Bradford J.; Kang, HyunSeon Christine; Cox, Veronica; Vega, Eduardo A.; Mizuno, Takashi; Pant, Shubham; Javle, Milind; Vauthey, Jean-Nicolas; Kawaguchi, Yoshikuni
Abstract: Background: In patients undergoing resection of intrahepatic cholangiocarcinoma (ICC), hypervascularity during the arterial phase of contrast-enhanced computed tomography (CT) is associated with better prognosis than hypovascularity. However, the prognostic implications of arterial enhancement pattern in patients with unresectable ICC are unknown. We assessed the prognostic implications of arterial enhancement pattern in patients with resectable and unresectable ICC. Methods: Consecutive patients who underwent surgery or gemcitabine-plus-cisplatin chemotherapy for ICC during 2003–2015 and CT with dynamic enhancement for diagnosis were included. After review by 2 radiologists, tumors were categorized according to the percentage of the tumor exhibiting arterial enhancement as hypervascular (>50% of tumor exhibiting enhancement), peripherally enhancing (10%–50%), and hypovascular (<10%). In each cohort (surgical and medical), overall survival (OS) curves were generated using the Kaplan-Meier method, and differences between curves were evaluated with Cox analysis. Results: The study included 56 patients treated surgically and 89 patients with unresectable ICC. Mean (standard deviation) tumor density in the hypervascular, peripherally enhancing, and hypovascular groups was 119.3 (45.2) Hounsfield units (HU), 72.1 (15.9) HU, and 59.9 (14.4) HU, respectively, in the surgical cohort and 93.6 (17.5) HU, 66.6 (16.2) HU, and 48.7 (14.3) HU, respectively, in the medical cohort. In both cohorts, the 5-year OS rate was significantly higher in the hypervascular group than in the hypovascular group (surgical, 67.6% vs 22.5%, P = .038; medical, 15.4% vs 0%, P = .030). In both cohorts, a Cox proportional hazards model analysis showed that hypervascularity was significantly associated with better OS. Conclusion: Hypervascularity during the arterial CT phase is a prognostic biomarker in patients undergoing ICC resection and patients with unresectable ICC. Highlights: Vascularity may reflect tumor biology in intrahepatic cholangiocarcinoma Vascularity classified into 3 grades in contrast-enhanced CT images Better prognosis of hypervascularity in both resectable and unresectable tumors